A high loading efficiency catalyst carrier and preparation method thereof

By using PEG of different molecular weights as template agents and pore-generating agents in the synthesis of alumina catalyst carriers, the problem of low support loading is solved, the specific surface area and pore volume are improved, and the catalyst performance with high load efficiency and long life is achieved.

CN118929711BActive Publication Date: 2024-12-17SHANDONG GONGQUAN CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411406424.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-17
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

During the synthesis process, the existing alumina catalyst support has problems such as low loading rate, small pore size and low specific surface area, which leads to poor catalyst performance and high cost of templates used, making it difficult to promote industrially.

Method used

By adding PEG with different molecular weights as template agents and pore-generating agents, the dispersant and pore-forming agents they play in the ammonium aluminum method are prepared to prepare an alumina precursor with a loose structure, and a high load efficiency is formed through the calcination process catalyst support.

Benefits of technology

The specific surface area and pore capacity of the catalyst support are improved, the loading rate and mechanical strength are enhanced, the service life of the catalyst is extended, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 15YN8XMNDSTE5ECK8ZRTMSGR2NCTAEGCVABD5Q4U
    Figure 15YN8XMNDSTE5ECK8ZRTMSGR2NCTAEGCVABD5Q4U
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalyst carrier preparation, and specifically relates to a catalyst carrier with high loading efficiency and a preparation method thereof, comprising the following steps: (1) adding aluminum salt and PEG template agent to deionized water to obtain an aluminum salt mixed solution; (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring; aging, centrifugation, washing, and obtaining a precipitate; (4) dispersing the precipitate and PEG porogen in deionized water, and placing in an oven to dry; (5) calcining treatment, and cooling to obtain a catalyst carrier with high loading efficiency. By adding PEG of different molecular weights to prepare a modified alumina precursor, and preparing an alumina catalyst carrier through a calcination process, the technical problems of low specific surface area, small pore size, and low loading rate of the existing carrier can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst carrier preparation, and particularly relates to a high-loading efficiency catalyst carrier and a preparation method thereof. Background Art

[0002] Catalysts used in industry are usually not composed of a single substance, but a mixture of multiple substances. According to the role these substances play in the catalyst, they can be divided into the following three categories: main catalyst, co-catalyst and catalyst carrier. The main catalyst is the main active component of the catalyst, and its role is to accelerate the catalytic reaction; the co-catalyst itself has no activity or very low activity, but its addition can greatly improve the activity, selectivity and stability of the catalyst; the catalyst carrier is a very important component of the catalyst. After determining the active component of the catalyst, the selection of the carrier will have a great impact on the catalytic reaction.

[0003] Catalyst carriers can improve the performance of catalysts in many ways. For example, they can increase the effective surface for reactions, provide reaction active centers and suitable pore structures, which can affect the activity and selectivity of the catalyst, and improve the mechanical strength, thermal stability and anti-poisoning performance of the catalyst.

[0004] Among them, alumina accounts for a large proportion of the use of catalyst carriers, which is mainly due to the fact that alumina carriers have most of the excellent properties that a catalyst carrier should have. Aluminum is the most abundant element in the earth's crust, with a mass fraction of up to 8.8% in the earth's crust. Although free aluminum has not been found in nature, aluminum is distributed all over the land and ocean. Now most of the aluminum resources are used to electrolyze the preparation of metallic aluminum, and the application of aluminum-containing compounds represented by alumina or aluminum hydroxide in other fields is also expanding. These fields include ceramics, abrasives, medicine, adsorption and catalysis, among which the one used in the catalytic field is usually called "activated alumina".

[0005] Because alumina has many excellent properties and has great application value in the fields of catalyst carriers, it has always attracted widespread attention from workers. Most of the existing technologies are to assemble porous alumina catalyst carriers by utilizing organic-inorganic ion interactions in water or solvents. The main methods for synthesizing alumina carriers are template method, solvothermal method and sol-gel method. Although there have been a lot of studies on synthesizing alumina carriers by using surfactants as templates, there are many problems in the synthesis process, such as the expensive templates used, which cannot be recycled, the high synthesis cost, and the inability to promote industrialization; when removing the template, the formed pores are easy to collapse due to the strong interaction between the template and alumina, etc., making it difficult to prepare catalyst carriers with high loading efficiency. Summary of the invention

[0006] In order to improve the deficiencies of the prior art, the purpose of the present invention is to provide a high-loading efficiency catalyst carrier and a preparation method thereof. A modified alumina precursor is prepared by adding PEG of different molecular weights, and an alumina catalyst carrier is prepared by a calcination process, which can solve the technical problems of low specific surface area, small pore size and low loading rate of the existing carrier.

[0007] The present invention adopts the following technical solution:

[0008] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0009] (1) adding aluminum salt and PEG template to deionized water, heating and dispersing them uniformly to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is (0.1-1):1; the number average molecular weight of PEG template is 5000-10000;

[0010] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 200-1000;

[0011] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to be greater than 7 with an alkali solution; after the addition is completed, aging, centrifuging, and washing to obtain a precipitate;

[0012] (4) dispersing the precipitate and the PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven; the number average molecular weight of the PEG porogen is 4000-7000; the mass ratio of the PEG porogen to the aluminum salt is (0.1-1):1;

[0013] (5) The dried product is placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier is obtained.

[0014] PEG is a common organic polymer substance in the field, and it is usually used as a surfactant and template to prepare alumina carriers. The cost of alumina carriers produced by the prior art is relatively high. Although the cooperation of PEG surfactants and templates of different molecular weights can improve the specific surface area and loading efficiency of alumina to a certain extent, this method is achieved by controlling the precipitation and aging process when preparing the gel, and the physical properties cannot be greatly changed. The prior art generally only adds templates or surfactants to aluminum salt solutions. On the basis of previous work, the inventor adjusts the timing of adding PEG to make PEG play the role of dispersant and pore-forming agent. First, PEG with different molecular weights is used as a template and surfactant, and a precursor precipitate with a loose structure is prepared by the ammonium aluminum method, and then a PEG pore-forming agent with a specific molecular weight is added. The PEG pore-forming agent not only plays a pore-forming role, but also can disperse and stabilize the precursor precipitate, inhibit the agglomeration between particles, and make the calcined product have a larger specific surface area. The PEG pore-forming agent is fully mixed with the precursor precipitate and occupies a certain volume in the molded particles. When the carrier is calcined at high temperature, the pore-forming agent will be converted into gas escape, thereby releasing the original space to form a certain number of macropores.

[0015] The present invention effectively increases the specific surface area and pore volume of the carrier by adjusting the molecular weight of the PEG porogen, thereby improving its loading efficiency. When the molecular weight of PEG is too small, the binding force between it and the precursor is weak, the porous structure of alumina is affected, and the pore volume is reduced; when the molecular weight is too large, the viscosity of the PEG micelle or micelle is large, the dispersion is uneven, and the composite with the precursor precipitation is also affected, and it cannot be evenly dispersed in the precursor, and it is difficult to play the role of a porogen.

[0016] At the same time, the amount of PEG will also affect the performance of the carrier. When the amount of PEG porogen is too small, it cannot fully fill the precursor precipitate, and the pore volume of the obtained alumina is small; when the amount is too much, not only does it reach the filling limit, but more importantly, the removal of the porogen during the calcination process may cause the pore structure to be destroyed, reducing the specific surface area and mechanical strength of the carrier.

[0017] In one embodiment, the aluminum salt in step (1) is one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride; and the aluminum salt concentration in the aluminum salt mixed solution is 0.1-0.3 mol / L.

[0018] In one embodiment, the heating temperature in step (1) is 50-60° C.; the dispersion is carried out by ultrasonic dispersion, and the frequency of the ultrasonic dispersion is 50-80 kHz.

[0019] In one embodiment, the ammonium salt in step (2) is one or more of ammonium bicarbonate, ammonium chloride, and ammonium sulfate; and the concentration of the ammonium salt is 0.6-1 mol / L.

[0020] In one embodiment, in step (2), the molar ratio of the ammonium salt to the aluminum salt is (5-10):1; and the mass ratio of the PEG surfactant to the aluminum salt is (0.01-0.05):1.

[0021] In one embodiment, the alkali solution in step (3) is one or more of ammonia water, sodium hydroxide solution, and potassium hydroxide solution; and the concentration of the alkali solution is 8-10 mol / L.

[0022] In one embodiment, the pH in step (3) is 8-10; and the washing is performed by alternating washing with deionized water and ethanol.

[0023] In one embodiment, the drying temperature in step (4) is 100-130°C.

[0024] In one embodiment, the calcination temperature in step (5) is 600-700° C. and the calcination time is 4-6 hours.

[0025] On the other hand, the present invention also provides a high-loading efficiency catalyst carrier. Compared with traditional alumina carriers, the alumina carrier has a larger specific surface area and can greatly improve the activity and service life of the catalyst.

[0026] The beneficial effects of the present invention are as follows:

[0027] 1. The alumina prepared by the present invention has a large pore volume and a high specific surface area, can provide more active centers, open diffusion space and a larger space for accommodating carbon deposits, sulfides and metals, has a high loading rate, and can better meet production needs.

[0028] 2. The alumina carrier of the present invention has a simple preparation process, and the raw materials are readily available. The surface chemical properties of the carrier can be adjusted while the pore structure of the carrier is effectively adjusted, and the application prospect is broad. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.

[0031] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.

[0032] It is worth noting that the raw materials used in the present invention are all common commercially available products, so their sources are not specifically limited.

[0033] In the following examples and comparative examples, the aluminum salt is aluminum nitrate, the ammonium salt is ammonium bicarbonate, and the alkali solution is 9 mol / L ammonia water.

[0034] Example 1

[0035] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0036] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.1:1; the number average molecular weight of PEG template is 5000; the aluminum salt concentration in the aluminum salt mixed solution is 0.1 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 50 kHz;

[0037] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 200; the concentration of the ammonium salt is 0.6 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 5:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.01:1;

[0038] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 8 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0039] (4) dispersing the precipitate and the PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven at 100°C; the number average molecular weight of the PEG porogen is 4000; and the mass ratio of the PEG porogen to the aluminum salt is 0.3:1;

[0040] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 600°C and the time was 6 hours.

[0041] Example 2

[0042] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0043] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.6:1; the number average molecular weight of PEG template is 10000; the aluminum salt concentration in the aluminum salt mixed solution is 0.3 mol / L; the heating temperature is 60°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 80 kHz;

[0044] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 1000; the concentration of the ammonium salt is 1 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 10:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.05:1;

[0045] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 10 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0046] (4) dispersing the precipitate and PEG porogen in deionized water, mechanically stirring them to obtain a uniform mixture, and then drying them in an oven at 130°C; the number average molecular weight of the PEG porogen is 7000; and the mass ratio of the PEG porogen to the aluminum salt is 0.6:1;

[0047] (5) The dried product is placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier is obtained; the calcination temperature is 700°C and the time is 4 hours.

[0048] Example 3

[0049] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0050] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.6:1; the number average molecular weight of PEG template is 5000; the aluminum salt concentration in the aluminum salt mixed solution is 0.3 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 80 kHz;

[0051] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 200; the concentration of the ammonium salt is 1 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 10:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.01:1;

[0052] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 8 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0053] (4) dispersing the precipitate and PEG porogen in deionized water, mechanically stirring them to obtain uniform mixture, and then drying them in an oven at 130°C; the number average molecular weight of the PEG porogen is 7000; and the mass ratio of the PEG porogen to the aluminum salt is 0.3:1;

[0054] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 600°C and the time was 6 hours.

[0055] Example 4

[0056] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0057] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.1:1; the number average molecular weight of PEG template is 9000; the aluminum salt concentration in the aluminum salt mixed solution is 0.1 mol / L; the heating temperature is 60°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 60 kHz;

[0058] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 800; the concentration of the ammonium salt is 0.6 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 6:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.05:1;

[0059] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 9 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0060] (4) dispersing the precipitate and PEG porogen in deionized water, mechanically stirring them to obtain a uniform mixture, and then drying them in an oven at 110°C; the number average molecular weight of the PEG porogen is 6000; and the mass ratio of the PEG porogen to the aluminum salt is 0.3:1;

[0061] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 690°C and the time was 5.2 h.

[0062] Example 5

[0063] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0064] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.2:1; the number average molecular weight of PEG template is 6000; the aluminum salt concentration in the aluminum salt mixed solution is 0.1 mol / L; the heating temperature is 52°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 60 kHz;

[0065] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 400; the concentration of the ammonium salt is 0.7 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 6:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.02:1;

[0066] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 8 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0067] (4) dispersing the precipitate and PEG porogen in deionized water, mechanically stirring them to obtain a uniform mixture, and then drying them in an oven at 120°C; the number average molecular weight of the PEG porogen is 5000; and the mass ratio of the PEG porogen to the aluminum salt is 0.4:1;

[0068] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 620°C and the time was 5.5 h.

[0069] Example 6

[0070] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0071] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.5:1; the number average molecular weight of PEG template is 8000; the aluminum salt concentration in the aluminum salt mixed solution is 0.15 mol / L; the heating temperature is 58°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 70 kHz;

[0072] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 800; the concentration of the ammonium salt is 0.8 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 9:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.04:1;

[0073] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 10 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0074] (4) dispersing the precipitate and PEG porogen in deionized water, mechanically stirring them to obtain a uniform mixture, and then drying them in an oven at 130°C; the number average molecular weight of the PEG porogen is 6000; and the mass ratio of the PEG porogen to the aluminum salt is 0.5:1;

[0075] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 680°C and the time was 4.5 h.

[0076] Example 7

[0077] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0078] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.3:1; the number average molecular weight of PEG template is 7000; the aluminum salt concentration in the aluminum salt mixed solution is 0.2 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 60 kHz;

[0079] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 600; the concentration of the ammonium salt is 0.8 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 7:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.03:1;

[0080] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 9 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0081] (4) dispersing the precipitate and the PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven at 100°C; the number average molecular weight of the PEG porogen is 5000; and the mass ratio of the PEG porogen to the aluminum salt is 0.4:1;

[0082] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 650°C and the time was 5.2 h.

[0083] Example 8

[0084] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0085] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of the PEG template to the aluminum salt is 1:1; the number average molecular weight of the PEG template is 7000; the aluminum salt concentration in the aluminum salt mixed solution is 0.2 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of the ultrasonic dispersion is 60 kHz;

[0086] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 600; the concentration of the ammonium salt is 0.8 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 7:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.03:1;

[0087] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 9 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0088] (4) dispersing the precipitate and the PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven at 100°C; the number average molecular weight of the PEG porogen is 5000; and the mass ratio of the PEG porogen to the aluminum salt is 0.4:1;

[0089] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 650°C and the time was 5.2 h.

[0090] Example 9

[0091] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0092] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.3:1; the number average molecular weight of PEG template is 7000; the aluminum salt concentration in the aluminum salt mixed solution is 0.2 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 60 kHz;

[0093] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 600; the concentration of the ammonium salt is 0.8 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 7:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.03:1;

[0094] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 9 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0095] (4) dispersing the precipitate and PEG porogen in deionized water, mechanically stirring them to obtain uniform mixture, and then drying them in an oven at 100°C; the number average molecular weight of the PEG porogen is 5000; and the mass ratio of the PEG porogen to the aluminum salt is 0.1:1;

[0096] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 650°C and the time was 5.2 h.

[0097] Example 10

[0098] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0099] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.3:1; the number average molecular weight of PEG template is 7000; the aluminum salt concentration in the aluminum salt mixed solution is 0.2 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 60 kHz;

[0100] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 600; the concentration of the ammonium salt is 0.8 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 7:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.03:1;

[0101] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 9 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0102] (4) dispersing the precipitate and the PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven at 100°C; the number average molecular weight of the PEG porogen is 5000; and the mass ratio of the PEG porogen to the aluminum salt is 1:1;

[0103] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 650°C and the time was 5.2 h.

[0104] Comparative Example 1

[0105] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0106] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.3:1; the number average molecular weight of PEG template is 7000; the aluminum salt concentration in the aluminum salt mixed solution is 0.2 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 60 kHz;

[0107] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 600; the concentration of the ammonium salt is 0.8 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 7:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.03:1;

[0108] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 9 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0109] (4) dispersing the precipitate and the PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven at 100°C; the number average molecular weight of the PEG porogen is 2000; and the mass ratio of the PEG porogen to the aluminum salt is 0.4:1;

[0110] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 650°C and the time was 5.2 h.

[0111] Comparative Example 2

[0112] A method for preparing a catalyst carrier with high loading efficiency comprises the following steps:

[0113] (1) Aluminum salt and PEG template are added to deionized water, and the mixture is heated and dispersed to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is 0.3:1; the number average molecular weight of PEG template is 7000; the aluminum salt concentration in the aluminum salt mixed solution is 0.2 mol / L; the heating temperature is 50°C; the dispersion is performed by ultrasonic dispersion, and the frequency of ultrasonic dispersion is 60 kHz;

[0114] (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 600; the concentration of the ammonium salt is 0.8 mol / L; the molar ratio of the ammonium salt to the aluminum salt is 7:1; the mass ratio of the PEG surfactant to the aluminum salt is 0.03:1;

[0115] (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to 9 with an alkali solution; after the addition is completed, aging, centrifuging, and washing alternately with deionized water and ethanol to obtain a precipitate;

[0116] (4) dispersing the precipitate and the PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven at 100°C; the number average molecular weight of the PEG porogen is 10,000; and the mass ratio of the PEG porogen to the aluminum salt is 0.4:1;

[0117] (5) The dried product was placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier was obtained; the calcination temperature was 650°C and the time was 5.2 h.

[0118] The specific surface area, pore size and pore volume of the high loading efficiency catalyst carriers prepared in Examples 1-10 and Comparative Examples 1-2 were tested by the BET method. A mixed impregnation solution of ammonium molybdate and basic nickel carbonate with ammonia water was prepared, and the active components were impregnated into the catalyst carriers prepared in Examples 1-10 and Comparative Examples 1-2 by an equal volume impregnation method, and the impregnated catalysts were dried and calcined to obtain catalysts. The catalysts were evaluated for desulfurization and denitrification in a residual oil hydroprocessing unit, and the specific results are shown in Table 1.

[0119]

[0120] As can be seen from Table 1, the present invention first uses PEG of different molecular weights as a template and surfactant, prepares a precursor precipitate with a loose structure by the ammonium aluminum method, and then adds a PEG porogen of a specific molecular weight to make the calcined product have a larger specific surface area. From Comparative Examples 1-2, it can be seen that the present invention effectively increases the specific surface area and pore volume of the carrier by adjusting the molecular weight of the PEG porogen, thereby improving its loading efficiency. When the molecular weight of PEG is too small, it leads to weak binding force with the precursor, the porous structure of alumina is affected, and the pore volume is reduced; when the molecular weight is too large, the viscosity of the PEG micelle or micelle is large, the dispersion is uneven, and it also affects the composite with the precursor precipitate, and it cannot be evenly dispersed in the precursor, and it is difficult to play the role of a porogen. Examples 1-10 show that the amount of PEG used in each step will also affect the performance of the carrier. When the amount of PEG porogen is small, the precursor precipitate cannot be fully filled, and the pore volume of the obtained alumina is small; when the amount is too much, not only the filling limit is reached, but more importantly, the pore structure may be destroyed due to the removal of the porogen during the calcination process, reducing the specific surface area of ​​the carrier.

[0121] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a catalyst carrier with high loading efficiency, characterized in that: It consists of the following steps: (1) adding aluminum salt and PEG template to deionized water, heating and dispersing them uniformly to obtain an aluminum salt mixed solution; the mass ratio of PEG template to aluminum salt is (0.1-1):1; the number average molecular weight of PEG template is 5000-10000; (2) adding ammonium salt and PEG surfactant to deionized water to obtain an ammonium salt mixed solution; the number average molecular weight of the PEG surfactant is 200-1000; the molar ratio of the ammonium salt to the aluminum salt is (5-10):1; the mass ratio of the PEG surfactant to the aluminum salt is (0.01-0.05):1; (3) adding the aluminum salt mixed solution dropwise to the ammonium salt mixed solution while stirring, and adjusting the pH value of the ammonium salt mixed solution to be greater than 7 with an alkali solution; after the addition is completed, aging, centrifuging, and washing to obtain a precipitate; (4) dispersing the precipitate and PEG porogen in deionized water, mechanically stirring them to obtain uniform dispersion, and then drying them in an oven; the number average molecular weight of the PEG porogen is 4000-7000; the mass ratio of the PEG porogen to the aluminum salt is (0.3-0.6):1; (5) The dried product is placed in a muffle furnace for calcination, and after cooling, a high-loading efficiency catalyst carrier is obtained.

2. The method for preparing a catalyst carrier with high loading efficiency according to claim 1, characterized in that: In step (1), the aluminum salt is one or more of aluminum nitrate, aluminum sulfate, and aluminum chloride; and in the aluminum salt mixed solution, the aluminum salt concentration is 0.1-0.3 mol / L.

3. The method for preparing a catalyst carrier with high loading efficiency according to claim 1, characterized in that: In step (1), the heating temperature is 50-60° C.; the dispersion is carried out by ultrasonic dispersion, and the frequency of the ultrasonic dispersion is 50-80 kHz.

4. The method for preparing a catalyst carrier with high loading efficiency according to claim 1, characterized in that: In step (2), the ammonium salt is one or more of ammonium bicarbonate, ammonium chloride and ammonium sulfate; and the concentration of the ammonium salt is 0.6-1 mol / L.

5. The method for preparing a catalyst carrier with high loading efficiency according to claim 1, characterized in that: In step (3), the alkali solution is one or more of ammonia water, sodium hydroxide solution, and potassium hydroxide solution; and the concentration of the alkali solution is 8-10 mol / L.

6. The method for preparing a catalyst carrier with high loading efficiency according to claim 1, characterized in that: In step (3), the pH is 8-10; and the washing is performed by alternating washing with deionized water and ethanol.

7. The method for preparing a catalyst carrier with high loading efficiency according to claim 1, characterized in that: The drying temperature in step (4) is 100-130°C.

8. The method for preparing a catalyst carrier with high loading efficiency according to claim 1, characterized in that: In step (5), the calcination temperature is 600-700°C and the calcination time is 4-6 hours.

9. A high loading efficiency catalyst carrier, characterized in that: The catalyst carrier having high loading efficiency is prepared by the preparation method of any one of claims 1 to 8.